Role of p53 and Ki-67 immunomarkers in oral premalignant lesions and squamous cell carcinoma: a hospital based study in BPKIHS (Journal of Pathology of Nepal, 2018)
Background: As most of the oral squamous cell carcinoma develop from precursor premalignant lesions, it would be helpful if the malignant transformation is detected early in premalignant state. The objective of the research was to study the role of immunohistochemical expression of p53 and Ki-67 in oral premalignant lesion and squamous cell carcinoma.Materials and Methods: The expression of immunomarkers p53 and Ki67 were studied on formalin fixed paraffin embedded tissue sections from human oral squamous mucosal lesion for duration of 1 year. Results: Of total 36 cases, 80% cases of keratosis without dysplasia showed basal pattern of p53 staining while 47.1% cases of squamous cell carcinoma showed p53 staining in all layers of epithelium. The median p53 Labelling Index of squamous cell carcinoma was more than those of keratosis with and without dysplasia though the result was statistically non-significant. 50.0% cases of keratosis without dysplasia and 83.3% cases of keratosis with dysplasia displayed Ki-67 immunostaining confined to basal and suprabasal layer whereas 94.1% cases of squamous cell carcinoma showed Ki-67 positivity in all layers of epithelium. Median Ki-67 Labelling Index increased from keratosis without dysplasia to keratosis with dysplasia to squamous cell carcinoma, difference being statistically significant. A positive and insignificant correlation was observed between p53 and Ki-67 Labelling Index.Conclusion: Increased expressions of Ki-67 and p53 in oral squamous cell carcinoma compared to premalignant lesion suggest that they may be useful indicator of malignant transformation in dysplastic lesion.